Tanggofun: The effectiveness of modified Snakes and Ladders games in improving children’s social skills - Piliang, Naila Rahma Suci; Tuti Rahmi; Yofa Putri Adinda; Rahmi Fadhila (Psikologia: Jurnal Pemikiran dan Penelitian Psikologi, 2025)
Social skills are a crucial component of early childhood development, facilitating social interaction and adjustment. The purpose of this study was to determine and test the effectiveness of modifying Snakes and Ladders games with social challenges to improve the social skills of kindergarten children. The research method used a pseudo-experiment with a two-group pretest-posttest design. In this study, the subjects consisted of 30 kindergarten children, divided into an experimental group and a control group. The experimental group participated in the “TanggoFun” game, which integrates social challenges, while the control group received no treatment. Data were collected through structured observation and analyzed using a paired samples t-test. The test results showed a significant increase in social skills scores for the children in the experimental group, whereas the control group showed no substantial change. The findings suggest that the modified Snakes and Ladders game is an effective learning medium for improving social skills in early childhood.